2002
DOI: 10.1042/bj3610547
|View full text |Cite
|
Sign up to set email alerts
|

A pH-dependent conformational transition of Aβ peptide and physicochemical properties of the conformers in the glial cell

Abstract: In the present study we identified the epitopes of antibodies against amyloid β-(1–42)-peptide (Aβ1–42): 4G8 reacted with peptides corresponding to residues 17–21, 6F/3D reacted with peptides corresponding to residues 9–14, and anti 5-10 reacted with peptides corresponding to residues 5–10. The study also yielded some insight into the Aβ1–42 structures resulting from differences in pH. An ELISA study using monoclonal antibodies showed that pH-dependent conformational changes occur in the 6F/3D and 4G8 epitopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Clone 6F3D is raised against Aβ 8−17 (DakoCytomation) [3,58]. Clone 4G8 (Signet) is raised against Aβ17-24 (Signet) [3,58]. Clone 12F4 is raised against Aβ 1−42 (Covance) and is reactive to C-terminus of Aβ and is specific for the isoform ending at the 42nd amino acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clone 6F3D is raised against Aβ 8−17 (DakoCytomation) [3,58]. Clone 4G8 (Signet) is raised against Aβ17-24 (Signet) [3,58]. Clone 12F4 is raised against Aβ 1−42 (Covance) and is reactive to C-terminus of Aβ and is specific for the isoform ending at the 42nd amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…Clone 6E10 is raised against Aβ 1−17 (Signet) [3,56,57]. Clone 6F3D is raised against Aβ 8−17 (DakoCytomation) [3,58]. Clone 4G8 (Signet) is raised against Aβ17-24 (Signet) [3,58].…”
Section: Introductionmentioning
confidence: 99%
“…A conformational transition of the prion protein has been detected by various mAbs (24 -26). The pH-dependent conformational transition of the Alzheimer ␤-amyloid peptide was monitored by their mAbs (27). Inhibition of the fibrillar aggregation of the Alzheimer ␤-amyloid peptide (28) and inhibition of prion transmission (29) have also been reported, based on the use of mAbs.…”
mentioning
confidence: 99%
“…Reverse structure Abeta , shorter fragments of the peptide (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and two unrelated peptides (bradykinin and bombesin) did not cause hydrolysis of fluorescein dibutyrate (supplementary Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…An ELISA study using mAbs showed that pH-dependent conformational changes occur in the region 10-24 [30]. This region comprises charged amino acids of pH-dependent protonation that may be involved in the peptide conformational changes.…”
Section: Discussionmentioning
confidence: 99%